ANTHROPOLOGICAL DIMENSIONS OF THE MODERN MUSICAL ART OF EASTERN EUROPE - Vereshchahina-Biliavska, Olena; Mozgalova, Nataliia; Baranovska, Iryna; Moskvichova, Yuliia; Cherkashyna, Olesia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The peculiarities of the world model and the human model in the Eastern European music art of the postmodern era were revealed. The research is based on a hermeneutical analysis of the contemporary Russian and Ukrainian composers’ works. The research method builds on the systematic and historical approaches. It allows to consider the individual musical text as a subsystem of a higher order system. The sociocultural context was considered. The scientific novelty consists in revealing the specifics of the Eastern European artists’ worldview of the last third of the XX and beginning of the XXI centuries. It is the consequence of studying their creativity in an anthropological dimension. The anthropological essence of the music of contemporary Ukrainian and Russian composers lies in a certain inconsistent polarity. The polarity is represented by the ironic and fragmented worldview combined with the religious quest. The awareness of the chaos and apocalyptic culture is combined with the religious support in its various manifestations. Therefore, the character in modern music has a dual essence. He is both marginal and a personality with strong spiritual support. In the works of contemporary Russian and Ukrainian composers, two postmodern worldview poles are organically combined: a destructive worldview and a desire for harmony. This polarity is caused by the crisis mentality of the modern post-totalitarian society.